ANALISIS HUKUM TERHADAP SERTIPIKAT HAK MILIK TANAH PASCA BERLAKUNYA OMNIBUS LAW CIPTA KERJA - Budi S.P. Nababan (Universitas Quality, 2021)
Land has a high value and is a place to live, earn a living, produce offspring, customs, and religious rituals, so to provide legal certainty and legal protection it is necessary to recognize land rights granted by the state through land registration as regulated in Government Regulation Number 24 of 1997 concerning Land Registration and Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration. The result of the land registration process is a land certificate which serves as a strong proof of ownership of land rights.